Estetika Busana Tari Melayu Jambi - Fatonah -; Mahdi Bahar; Hartati M (Institut Seni Indonesia Denpasar, 2022)
This research aimed to know the concept of dress aesthetics and art of traditional and creative dance of Jambi Malay, and dress development of Jambi Malay dance could be seen from a dress of traditional dance, creative dance, and contemporary dance. The research result was expected to be one of Jambi Malay culture inventory in social science. The research method used is a descriptive qualitative research method with a symbolic interaction approach. The background of the people of Jambi city which is multicultural makes Jambi city rich in cultural diversity, one of which is dance. Dance dress is included as an important element in dance performance. Dance dress is a symbol of aesthetics and artistry in dance performances. The dress wisdom of Malay dance is not separated from aesthetic and artistic concepts based on concepts of custom and Islam. The concept is based on message of Jambi culture, “adat bersendikan syarak, syarak bersendikan kitabullah, syarak mengato adat memakai”. The research conclusion is that the ideal dress aesthetically according to Jambi Malay tradition after converting to Islam is a dress that covers the genitals. Artistically it is the dress that is lost when moving, with not too much design based on Islamic custom and law while color is usually natural color and adapted.